2010
DOI: 10.1103/physrevb.82.134106
|View full text |Cite
|
Sign up to set email alerts
|

First-principles accurate total energy surfaces for polar structural distortions ofBaTiO3,PbTiO3, andet al.

Abstract: Specific forms of the exchange correlation energy functionals in first-principles density functional theory-based calculations, such as the local density approximation (LDA) and generalized-gradient approximations (GGA), give rise to structural lattice parameters with typical errors of −2 % and 2 %. Due to a strong coupling between structure and polarization, the order parameter of ferroelectric transitions, they result in large errors in estimation of temperature dependent ferroelectric structural transition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 27 publications
8
79
1
1
Order By: Relevance
“…6), which is similar to the dispersion obtained in earlier simulations using WC-GGA-based parameters 7 . The short-range interaction gives the most unstable mode at the X point ( see FIG.…”
Section: Effective Hamiltoniansupporting
confidence: 78%
See 1 more Smart Citation
“…6), which is similar to the dispersion obtained in earlier simulations using WC-GGA-based parameters 7 . The short-range interaction gives the most unstable mode at the X point ( see FIG.…”
Section: Effective Hamiltoniansupporting
confidence: 78%
“…Instead, an approximate approach is adopted that uses an effective Hamiltonian, which focuses on the low-energy structural configurations in MD or MC simulations 7,8 . Thus, there are two sources of errors in first-principles description of ferroelectric transitions: (a) ones arising from the choice of DFT functional, and (b) ones arising from the truncation of the set of configurations through the effective Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
“…17, we perform first-principles calculations to determine a set of parameters of H eff for SrTiO 3 (See Table I). We averaged the parameters of H eff of BaTiO 3 in Ref.…”
Section: A Results Of First-principles Calculation Andmentioning
confidence: 99%
“…We averaged the parameters of H eff of BaTiO 3 in Ref. 17 and those of H eff of SrTiO 3 (See Table I). It is found that this set of parameters indeed reproduces the three transition temperatures of (Ba 1/2 Sr 1/2 )TiO 3 as depicted in Fig.…”
Section: A Results Of First-principles Calculation Andmentioning
confidence: 99%
See 1 more Smart Citation